KUALITAS PENDUDUK DI PESISIR PANTAI TELUK PALU - Syarifuddin Syarifuddin (MEKTEK, 2012)
A house is a basic need for each family to reach a prosperity and familiy future. Physical of house is one of determining factor to get a healthy house. This paper, describe physical of a house of Palu Town inhibitant near Palu bay in 2003 in terms of city development and architectural rule. . The physical of a house which is observed such as : area of the house and yard, type of building material and house wall condition, type of slab and roof material, the existence of ventilation, lighting condition inside the house, and condition of drainage. The report is conducted through descriptive and analytical approach.